2010
DOI: 10.1007/s12564-010-9096-y
|View full text |Cite
|
Sign up to set email alerts
|

Correlational analysis of ordinal data: from Pearson’s r to Bayesian polychoric correlation

Abstract: Correlational analyses are one of the most popular quantitative methods, yet also one of the mostly frequently misused methods in social and behavioral research, especially when analyzing ordinal data from Likert or other rating scales. Although several correlational analysis options have been developed for ordinal data, there seems to be a lack of didactically written literature illustrating the appropriate use and differences among them. The purpose of this paper is to provide a synthesis of correlational an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 16 publications
2
64
0
11
Order By: Relevance
“…In this study criterion validity with DASH was moderate (r=0,68), which was lower than in both the original and the French-Canadian versions (r=0,85). Researchers describe some factors such as sample size and characteristics of the sample that may affect the size of r in Pearson analysis (54)(55)(56). In this study correlation might be lower than other researchers have reported because of differences in the characteristics of the sample.…”
Section: Discussionmentioning
confidence: 72%
“…In this study criterion validity with DASH was moderate (r=0,68), which was lower than in both the original and the French-Canadian versions (r=0,85). Researchers describe some factors such as sample size and characteristics of the sample that may affect the size of r in Pearson analysis (54)(55)(56). In this study correlation might be lower than other researchers have reported because of differences in the characteristics of the sample.…”
Section: Discussionmentioning
confidence: 72%
“…invasiveness and time since introduction; Choi et al . ). Finally, the responses to open‐ended questions (e.g.…”
Section: Methodsmentioning
confidence: 97%
“…All structural equation modeling was conducted using R statistical software with the “lavaan” package (Rosseel 2012). Because the variables (i.e., PICTS-SV items) included in the CFA were on an ordinal scale of measurement, we used polychoric correlations rather than Pearson product-moment correlations (Choi et al 2010; Holgado–Tello et al 2010). Any zero values in the 4×4 contingency tables used to calculate the polychoric correlations were changed to .001 (Savalei 2011; Y. Rosseel, personal communication, September 18, 2014).…”
Section: Resultsmentioning
confidence: 99%